Selective Reduction in Complex Monochorionic Gestations - Bebbington, Michael (American Journal of Perinatology, 2014)
The early determination of chorionicity in twin gestations is a critical factor in the management of twin gestations. While twins and higher order multiple gestations have increased risks of almost any complication of pregnancy, those pregnancies involving a monochorionic (MC) twin pair are at an especially high risk. The presence of vascular anastomoses within a MC placenta creates risk for discordant malformations, twin reversed arterial perfusion sequence, twin-to-twin transfusion syndrome, or severe selective intrauterine growth restriction. While selective reduction of higher order multiple pregnancies is performed to reduce pregnancy-related risks and improve overall outcomes, selective reduction is also an important management strategy in situations where MC pregnancies develop complex complications. This procedure can be lifesaving for the cotwin by preventing intrauterine demise or extreme prematurity. There are several techniques that can be considered, each with its own advantages and disadvantages.
Keywords: bipolar cord coagulation; radiofrequency ablation; complicated monochorionic twin pregnancy; discordant fetal anomalies; selective feticide; selective growth restriction; twin-to-twin transfusion syndrome